Digitalisasi Administrasi Desa melalui Implementasi OpenSID di Desa Aikmel: Pendekatan Deskriptif-Partisipatif KKN UNRAM - Muhammad Gilang Hanggara; Zaskia Elvina Dewi; Abdul Salam; Muhammad Prasetya Putra; Halisah Halisah; Nur Masita; Maharani Maharani; Yennysa Puspita Dewi; Sutina Ariyani; Rajata Hayya Wibowo; Leni Triana Febrianti; Iwan Kusmayadi (Indonesian Journal of Education and Community Services, 2026)
The implementation of the Village Information System (SID) represents a strategic step in enhancing the quality of administrative services through the digitalization of population data management. Prior to the SID implementation, Aikmel Village encountered various obstacles, including non-digitalized data management and manual administrative processes, which led to potential delays and recording errors. This article aims to describe the implementation of an OpenSID-based system to support administrative service efficiency through the Community Service Program (KKN) of the University of Mataram. The methodology employed includes participatory observation, population data updating and digitalization, technical assistance for village officials, and the evaluation of correspondence services. The results demonstrate a significant transformation from the initial absence of a digital database to an integrated system with 9,499 successfully digitalized population records. The utilization of SID supports administrative services with an average of seven documents processed per workday, while simultaneously improving service time efficiency, digital archiving organization, and data access accuracy. The success of this implementation is influenced by the quality of data digitalization, infrastructure readiness, and the active involvement of village officials in system management. The implementation of SID contributes to the strengthening of data-based village administrative governance and holds sustainable potential in supporting transparency and more effective village development planning.